Pengaruh Total Operating Expenses Dan Income Tax Expense Terhadap Net Income For The Year Pada PT. Indocement Tunggal Prakasa Tbk. Periode 2010-2019 - Gina Saila Sofiah; Yadi Janwari; Widiawati; Vemy Suci Asih (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
The company's performance is based on how much profit it generates. The profit generated by the company can not be separated from operational costs and taxes that must be spent. Therefore, operating costs and income tax are considered as expenses in the company that can reduce net profit. This study aims to find out the effect of Total Operating Expenses and Income Tax Expense on Net Income For The Year of PT. Indocement Tunggal Prakasa Tbk. The method used is descriptive method with quantitative approach using statistical method to test hypotheses. The results showed that Total Operating Expenses partially negatively had no significant effect on Net Income For The Year, with a contribution of 13.4%. Income Tax Expense partially positively had a significant effect on Net Income For The Year, with a contribution of 72.7%. Total Operating Expenses and Income Tax Expense simultaneously had a significant effect on Net Income For The Year, with a contribution of 72.7% .